The influence of music performance anxiety on career expectations of early musical career students: self-efficacy as a moderator - Wang, Qi-ran; Yang, Rong (Frontiers in Psychology, 2024)
Music performance anxiety (MPA) is recognized as a distinct emotional behavior rather than merely a motor control disorder and is influenced by specific conditioning experiences. This study investigates the interrelationships between MPA, self-efficacy, and future career expectations among music students within the Chinese context. The participants of this study were 340 high school students majoring in music education and performance, drawn from three music schools in China. Data were collected using several questionnaires: the MPA Inventory for Adolescents (MPAI-A), the Self-Efficacy Formative Questionnaire, and the Career Futures Inventory (CFI). The findings indicate that MPA is negatively associated with self-efficacy and future career expectations. Additionally, self-efficacy acts as a partial moderator between MPA and career expectations, suggesting that enhancing the self-efficacy of music students can boost their future career aspirations and mitigate the adverse effects of MPA. This research explores the complex relationships among MPA, selfefficacy, and future career expectations, emphasizing the importance of curriculum and pedagogical strategies in music schools. Music students with high levels of self-efficacy may exhibit more confidence and stable performances before audiences. According to the panel regression analysis, self-efficacy significantly positively influences career expectations. An appropriate educational environment and supportive pedagogical approaches to MPA can foster the early career development of musicians.& Bernaras, 2020). Its influence extends beyond musical aptitude, training, and levels of preparation to include intrinsic and extrinsic cognitive, as well as cultural factors (Papageorgi et al., 2007;Salmon, 1990). For instance, seasoned musicians may experience less anxiety arousal compared to inexperienced ones, who may peak during performances (Butzer et al., 2016;Ryan, 2004;Salmon et al., 1989). Furthermore, individual variables such as gender, experience, and weekly practice hours exhibit distinct correlations with MPA, especially when comparing early-career students to professional musicians (Biasutti & Concina, 2014). The manifestations of MPA include a variety of symptoms that appear through a combination of subjective feelings, cognitive, physical (Sabino et al., 2020), and behavioral changes (D.